2018
DOI: 10.3389/fimmu.2018.00712
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Helicobacter pylori and Atrophic Gastritis Influence Lactobacillus in Gut Microbiota in a Japanese Population

Abstract: BackgroundSuppression of gastric acid by proton pump inhibitors is associated with the increase of Lactobacillus in human gut microbiota. Gastric acid secretion is also suppressed by Helicobacter pylori infection and following atrophic gastritis. However, few studies have examined the association between H. pylori infection and Lactobacillus species in gut microbiota particularly in Japan.MethodsA total of 1,123 adult subjects who participated in a health survey in Hirosaki City were studied. Infection of H. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…Currently, a great number of studies have shown that H pylori infection not only affects the structure of the gastric microbiota but also induces the alterations of gut microbiota in both human and animal models . A previous study from Japan showed that species of Lactobacillus in the gut microbiota were associated with H pylori infection and that the composition ratio of each Lactobacillus species was different between H pylori ‐positive and H pylori ‐negative subjects . A study by Gao et al showed that the observed species and Shannon index were increased in subjects with past or current H pylori infection compared with those of H pylori ‐negative subjects, and a differential abundance of bacteria was identified among these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a great number of studies have shown that H pylori infection not only affects the structure of the gastric microbiota but also induces the alterations of gut microbiota in both human and animal models . A previous study from Japan showed that species of Lactobacillus in the gut microbiota were associated with H pylori infection and that the composition ratio of each Lactobacillus species was different between H pylori ‐positive and H pylori ‐negative subjects . A study by Gao et al showed that the observed species and Shannon index were increased in subjects with past or current H pylori infection compared with those of H pylori ‐negative subjects, and a differential abundance of bacteria was identified among these groups.…”
Section: Discussionmentioning
confidence: 99%
“…of Lactobacillus in the gut microbiota were associated with H pylori infection and that the composition ratio of each Lactobacillus species was different between H pylori-positive and H pylori-negative subjects. 31 A study by Gao et al 19 showed that the observed species and Shannon index were increased in subjects with past or current H pylori infection compared with those of H pylori-negative subjects, and a differential abundance of bacteria was identified among these groups. Consistent with these studies, we observed that H pyloriinfected individuals had higher gut microbial diversity than those without infection, and positive H pylori status was associated with increased relative abundance of Alistipes and decreased abundance of Lachnoclostridium.…”
Section: Discussionmentioning
confidence: 99%
“… 31,32 Strikingly, most studies investigating the relationship between H pylori infection and gut microbial diversity provided a positive correlation (Figure 2; Table 2). 31,33‐36 As higher microbial diversity is usually associated with an overall better health state, it will be interesting to explore whether the increased intestinal microbial diversity upon H pylori infection provides some beneficial effects to the host. Significant differences in microbial community structures were found between the H pylori ‐infected and negative control groups 33‐36 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 99%
“… 31,33‐36 As higher microbial diversity is usually associated with an overall better health state, it will be interesting to explore whether the increased intestinal microbial diversity upon H pylori infection provides some beneficial effects to the host. Significant differences in microbial community structures were found between the H pylori ‐infected and negative control groups 33‐36 . The compositional analysis at the phylum level discovered that the abundance of Proteobacteria significantly increased in infected individuals, which could be due to the transfer of Helicobacter from the stomach to the intestinal lumen 6,34 .…”
Section: Gastrointestinal Microbiota Reshaping Upon H Pylori Infectionmentioning
confidence: 99%
“…The reduced acid secretion induced by H. pylori infection can lead to alternations in the composition of gut microbiota, similar to PPI use. Indeed, we recently reported that the abundance of Lactobacillus in the gut microbiota was altered by H. pylori infection and atrophic gastritis [10]. However, the influence of H. pylori infection on the composition of the gut microbiota has not been well characterized, and only a small number of studies have examined the influence of eradication therapy [11][12][13].…”
Section: Introductionmentioning
confidence: 99%